Will the last person left please turn on the lights ; Ceboom or doomn ; Rizal lights and sound [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1992)
Reports on the powerplant shortage Mindanao and NAPOCOR irregularities. The economic success of Cebu was criticized that the boom has taken place at the expense of slum dwellers who have been deprived of their rights. Focuses the 95th death anniversary of Jose Rizal and the sculptural tableau of his martyrdom in his honor.
Will the last person left please turn on the lights (17 min.) -- Ceboom or doomn (15 min.) -- Rizal lights and sound (15 min.)
VHS.
Keywords: Rizal, Jose, 1861-1896 -- Germany; National Power Corporation -- Corrupt practices; Squatters -- Philippines -- Cebu City; Cebu City -- Economic conditions